(untitled) (Communications in Computational Physics, 2006)
Two algorithms for dwell time adjustment are evaluated under the same polishing conditions that involve tool and work distributions. Both methods are based on Preston's hypothesis. The first method is a convolution algorithm based on the Fast Fourier Transform. The second is an iterative method based on a constraint problem, extended from a one-dimensional formulation to address a two-dimensional problem. Both methods are investigated for their computational cost, accuracy, and polishing shapes. The convolution method has high accuracy and high speed. The constraint problem on the other hand is slow even when it requires larger memory and thus is more costly. However, unlike the other case a negative region in the polishing shape is not predicted here. Furthermore, new techniques are devised by combining the two methods.